The Erasure of Empowered Gossip in Academia - Adkins, Karen C. (Nouvelle Revue Synergies Canada)

(untitled) (University of Guelph, School of Languages and Literatures, 2014)
This article analyzes two recent instances of academic gossip becoming publicized, and suggests that the varying results of these case studies (so similar in other respects) reflects the fragile nature and tenuous status of institutional gossip.  It is both a crucial tool for individuals to understand and function within workplaces, but its very effectiveness in popularizing critique makes it easy for those with status to critique it.